Web usage analysis of Pillar 3 disclosed information by deposit customers in turbulent times. (15th December 2021) - Munk, Michal; Pilkova, Anna; Benko, Lubomir; Blazekova, Petra; Svec, Peter
Highlights: Stakeholders' interest in Pillar 3 disclosures is low even during turbulent times. During turbulent times, strategic issues have the highest peak in attractiveness. After turbulent times, Pillar3 categories have weak interest. Enhancement of interest of key stakeholders in Pillar 3 disclosures requires major changes. The Pillar 3 disclosures are most attractive at the beginning and at the end of the year. Abstract: Market discipline has been a scrutinized area since the last financial crisis in 2008. Regulators strengthened their role particularly through Pillar 3 in Basel III. However, there are still some aspects of market discipline that deserve special attention to avoid future failures. This study focuses on the analysis of the interest and behaviour of deposit stakeholders based on website data dedicated to disclosures of commercial bank in Slovakia during and after turbulent times (period 2009–2012). The data consists of log files, and web mining techniques were applied (the modelling of web user behaviour in dependence on time - based on the proposals of the authors). The results show that also in turbulent times, stakeholders' interest in Pillar 3 disclosures is low (in line with (Munk, Pilkova, Benko, & Blažeková, 2017 )) and the highest interest was identified for the Pricing List category. After turbulent times, Pillar 3 categories (Pillar 3 related information and Pillar 3 disclosures) have weak interest, with peaks at the beginning of the year, and the highest increase was in the Business Conditions category. The results suggest that the enhancement of interest of key stakeholders in disclosures inevitably requires changes to deliver sufficient disclosure data structures and to design a disclosure policy that fulfils regulatory expectations.